Men with Gender Minority as a Beauty Influencer on TikTok - Agustina, Shola Brela (Journal of Development and Social Change, 2022)
The purpose of this researceh are to (1)Ffind out and understand how influencers show their virtual identity on TikTok, (2) Find out and understand the virtual interaction between influencers and their followers o TikTok, (3) Understand the reconstruction of masculinity from influencers through virtual spaces on TikTok. The thory used for this research is Dramaturgy of Ervin Goffman with a qualitative method with virtual etnography strategic method of this research. The data collection techniques was conducted by interview with purposive sampling and participant observation. The informants  in this research consisted of 4 male beauty influencers and 4 TikTok users who were follow and viewer of beauty influencer. The results of this studyindicate that the virtual identity that are presented occurs because of a process, starting from beginning of users TikTok then becoming an influencer and then producing a content so as to produce a virtual identity that are dividing into 5 characterisrics: (1) Break The Rules, (2) Honest Reviewer, (3) Build Your Own Personality, (4) Me but not myself, (5) Different is Unique. The next resuts is regarding the interaction made with followers that can be occur through comments and live streaming which can be in the form of constructive interactions, namely by interaction through positive comments and dropping interactions throught negative comments. Another results is that masculinity reconstruction occurs in beauty influencers because on social media the impression of masculinity becomes blurred and it is can be switch and change meaning according to the personal perspective, the aspects that reconstruction are physical and emotional.Keywords: Virtual Idenity, Virtual Interactions, Beauty Influencers, TikTok, Masculinity